2017
DOI: 10.1515/achi-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Condensation Reactions Effectively Catalysed by Lewis Acid

Abstract: A complex of manganese (III) and R,R-1,2-Diaminocyclohexane linked ketopinic acid ligand was synthesized and utilised as catalyst in the aldol condensation reactions of benzaldehyde with various aliphatic ketones to furnish products with excellent yield of 99%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The deactivation of the active sites responsible for LA formation shown in the left-hand side graph of Figure is not surprising. In fact, Lewis acid sites are reported to be active in condensation reactions in the absence of a base. ,, Therefore, it is likely that the macromolecules detected by NMR and ATR IR spectroscopy are slowly growing and covering the Lewis acid sites responsible for LA production. This hypothesis explains the decrease in the LA yield detected over 30 h and reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The deactivation of the active sites responsible for LA formation shown in the left-hand side graph of Figure is not surprising. In fact, Lewis acid sites are reported to be active in condensation reactions in the absence of a base. ,, Therefore, it is likely that the macromolecules detected by NMR and ATR IR spectroscopy are slowly growing and covering the Lewis acid sites responsible for LA production. This hypothesis explains the decrease in the LA yield detected over 30 h and reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the dehydration of THFA to DHP in the presence of H 2 O is unlikely for the same reason. In contrast, in the absence of co‐fed H 2 O, the surface coverage of HVAL increased over time favoring side reactions, such as the aldol condensation and the Tishchenko reaction, that are catalyzed by Lewis acid sites [59–61] . Sato and coworkers demonstrated that a commercial SiO 2 sample possessed a discrete amount of weak acid sites and that it was active in the vapor phase aldol condensation of butanal [62] .…”
Section: Resultsmentioning
confidence: 99%